Resources - from math to movies [science fiction film making]. - Cass, S.
This paper presents an interview with Shane Carruth about his experiences in making the independent science-fiction film about time travel, called Primer, winner of the Alfred P. Sloan prize for advancing science and technology in film.
Keywords: Primer; Computer science; Film making; Math applications; Science-fiction film; Time machine